Giant Merkel Cell Carcinoma Masquerading as a Benign Cyst on the Buttock of an African American Man - Marissa J. Perman; Janelle M. King; Laurel L. Leithauser; Hugh M. Gloster (Case Reports in Oncological Medicine)
We report a case of a 60-year-old African American man who presented with a 4-year history of a previously asymptomatic, recently enlarging nodule on his left buttock, which was initially presumed to be an epidermoid cyst. Physical examination revealed a large, fixed, subcutaneous tumor, and a biopsy revealed merkel cell carcinoma. Immunohistochemical staining was positive for pankeratin, CAM 5.2, synaptophysin, and CD56 and negative for CK7, CK20, TTF-1, chromogranin, CD3, CD20, CD57, MART1, and HMB 45. The patient underwent wide local excision of the lesion with removal of the fascia overlying the gluteus and full body positron emission tomography (PET) and was found to have Stage IIb disease. He subsequently received adjuvant radiotherapy limited to the tumor bed at a dose of 60 gray.